2020
DOI: 10.1002/erv.2768
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms rather than executive functioning predict group cognitive behavioural therapy outcome in binge eating disorder

Abstract: Executive functions play an important role in mediating self-control and selfregulation. It has been suggested that the inability to control eating in Binge Eating Disorder (BED) may indicate inefficiencies in executive functioning. This study investigated whether executive functioning predicted cognitive behavioural therapy outcome in BED while accounting for other possible predictors: depressive symptoms, interpersonal factors, eating disorder psychopathology, and self-esteem. Executive functioning and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
(79 reference statements)
1
15
1
Order By: Relevance
“…Present results also corroborate and extend the understanding of the recent findings of Dingemans and colleagues (Dingemans et al., 2020). Authors evaluated whether EF on entry predicted the outcome of cognitive behavioural therapy for patients with BED, when accounting for depressive symptoms, and found that while EF were only weakly predictive, depression severity was associated with 50% reduction in ED severity and/or abstinence of objective binge eating.…”
Section: Discussionsupporting
confidence: 93%
“…Present results also corroborate and extend the understanding of the recent findings of Dingemans and colleagues (Dingemans et al., 2020). Authors evaluated whether EF on entry predicted the outcome of cognitive behavioural therapy for patients with BED, when accounting for depressive symptoms, and found that while EF were only weakly predictive, depression severity was associated with 50% reduction in ED severity and/or abstinence of objective binge eating.…”
Section: Discussionsupporting
confidence: 93%
“…In general terms, some of these cognitive impairments seem to be remediable 79 . However, some studies found a greater relevance of comorbid psychopathology in individuals with BED, namely depressive symptomatology, than cognitive dysfunction for therapy outcomes 80 . Decision-making is a complex cognitive process, involving conscious and habitual components, which ultimately results in the choice of an outcome over other alternatives.…”
Section: [H2] Cognitive Impairments In Bedmentioning
confidence: 99%
“…In individuals with BPD, emptiness has been associated with lower levels of daily positive affect and higher levels of depression (Harpoth et al, 2021; Klonsky, 2008). Severity of depressive symptoms and greater anhedonia have been found to significantly predict ED symptom severity and successful treatment for EDs (Dingemans et al, 2020; Dolan et al, 2021; Vall & Wade, 2015); thus, emptiness may be an important BPD symptom to target when treating EDs. Finally, BPD treatment outcome studies have found that anger predicts drop‐out from treatment (Wnuk et al, 2013) and may likewise contribute to dropout in treatment for EDs.…”
Section: Introductionmentioning
confidence: 99%